Analysis of Coconut Coir Waste Utilization on Green Productivity-Based Plant Pot Crafting Planning (Case Study in Ice Coconut Water Pak Mamat) - Ulfa, Mau Lidia (International Journal of Science, Engineering, and Information Technology, 2024)
Coconut (Cocos Nucifera L) is a versatile plant or has high economic value. All parts of the coconut tree can be used for human benefit, so this tree is often referred to as the tree of life. Coconut fiber can be used as a product that has high value and can increase farmers' income. It is processed to produce products from coconut fiber that can increase profits and maintain environmental sustainability. Processing of coconut fruit, especially its derivative products, still has considerable opportunities. The coconut fruit processing industry in general is still focused on processing fruit flesh as the main product, while industries that process by-products such as water, coir, and coconut shells are still processed traditionally. This coconut fiber can be developed into a variety of products. Waste from ice sellers is one of the coconut wastes that can be used to increase profits and preserve the environment. The research process was carried out using a case study of the ice business with Pak Mamat which was observed through a process of observation and interviews, the processing of the waste contained in this process was carried out by utilizing it into handicraft items, namely plant pots made from coconut fiber waste